Estudo de segurança farmacológica do ácido caurenóico, um diterpeno bioativo isolado do óleo resina de Copaifera langsdorfii - Cunha, Karina Moreira de Alencar (2006)
Copaíba oil-resin from Copaifera langsdorfii is a popular natural health product used for the treatment of sore throat, urinary and pulmonary affections, and to promote healing of ulcers and wounds. The oil-resin contains various terpenoid components including kaurenoic acid (KA), a principal diterpenoid that manifests anti-inflammatory, antinociceptive, diuretic, vasodilator and hypoglycemic effects. Besides, KA at higher concentrations demonstrates genotoxicity in the tests of Comet and Micronucleus in vitro. Because of this genotoxic potential, it needs to be restrained the concentration of KA in commercial preparations of copaiba oil. The present work therefore aims to assess the safety of KA through cytotoxicity and acute toxicity tests, studying the effects on central nervous system (CNS), cardiovascular, respiratory and reproductive systems in vivo and in vitro. The toxicity tests were performed using Brine shrimp (Artemia sp.) larvae, rat and human erythrocytes, tumor cell lines, and sea urchin (Lytechinus variegatus) gametes and embryos. In the study of cardiovascular effects, KA was examined on rat ECG and blood pressure, rat or guinea pig isolated perfused heart, atria, aorta, and on rat mesenteric perfusion. The reproductive effects of KA were examined on implantation and organogenesis in mice. The results obtained from the open field and rota rod tests did not reveal any apparent toxicity of KA to the CNS. The KA up to an oral dose of 1g/kg in mice produced no measurable toxicity and the 50% lethal dose (LD50) through a 72h oral toxicity study could not be established. On the other hand, KA showed a very high toxicity to Artemia sp. (LC50 2.00 ± 0.48g/mL = 6,6M); hemolytic activity (EC50 of 74M and 56M on rat and human RBCs, respectively); manifested antiproliferative effects (78 M) against MCF-7 (95% inhibition) and HCT-8 (45% inhibition); embryotoxicity to L. variegates, impaired the fertilization and development of blastula and larval stages with an IC50 of 84.2 M, 44.7M and <10M, respectively). On ECG, there was no significant alteration in the QT interval but did produce bradycardia and showed a tendency to prolong the PR interval. KA (10mg/Kg) induced a hypotensive response in anesthetized normotensive rats. On perfused rat heart, KA at 1000 g showed a negative inotropic effect (59%) partially reverted by adrenaline (300ng). A similar negative inotropism was evidenced in guinea pig heart (KA 300g, 47% and 1000g, 50%). In isolated atrium, KA (1-1000g/mL = 3M – 3mM) demonstrated neither bradycardia nor a change in cardiac contractile force. In aortic rings pre-contracted by phenylephrine (1-10M), KA (1-300g/mL = 3M - 1mM) failed to produce a relaxant effect but, however, pre-incubation with KA (50g/mL = 160M) significantly inhibited the maximal contraction induced by phenylephrine as evidenced by a rightward shift in the concentration-response curve. KA, at oral doses up to 50mg/Kg was found to be free from estrogenic or antiestrogenic effects in mice. Nevertheless, 50 mg/Kg treatment with KA promoted heavy embryonic loss, and at 25mg/Kg, although it caused no such impairment but significantly affected the maternal weight gain during pregnancy. During the organogenesis phase, a reduction in maternal, fetal and placental weight gains was observed. Besides, KA treatment groups showed markedly delayed fetal ossifications (25mg/Kg) and an adverse pregnancy outcome (50mg/Kg). In conclusion, the data obtained from in vivo experimentation suggest that KA, at the doses tested, is apparently safe and free from undesirable effects in all the studied organ systems (core battery of safety pharmacology studies) except the reproductive one (supplemental studies), where in its antiproliferative and anti-inflammatory actions may possibly contribute to impaired pregnancy outcome. Therefore, a caution needs to be exercised in the use of copaiba oil resin during pregnancy.